Antimicrobial Activity of Ethanol Extract of Centella asiatica Leaves on Proteus mirabilis, Proteus vulgaris, and Yersinia enterocolitica in vitro - Salwa Putri Qurrotuaini; Nurul Wiqoyah; Arifa Mustika (Molecular and Cellular Biomedical Sciences, 2022)
Background: Centella asiatica leaves ethanol extract (CALEE) has higher concentration compared to other structures within the plant. The extract contains alkaloids, saponins and flavonoids, which play an active role as antioxidant and antibacterial. Current study aimed to determine the effect of CALEE on Proteus mirabilis, Proteus vulgaris, and Yersinia enterocolitica, Gram-negative bacteria that cause diarrhea. Materials and methods: Simplicia of C. asiatica leaves was dissolved in 96% ethanol and macerated to get condensed extract, which then produced a concentration of 1 g/mL. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined to assess the effectiveness of CALEE on P. mirabilis, P. vulgaris, and Y. enterocolitica. MIC was determined through serial dilution test with Mueller Hinton broth media. After incubation, the bacteria were streaked on nutrient agar or McConkey agar to determine the MBC. Results: The MIC value of CALEE could not be determined since the color of CALEE was dark, hence the turbidity could not be compared. CALEE had the same MBC value (0.25 g/mL) in all bacteria species used in this study. Conclusion: CALEE is effective against Gram-negative bacteria, such as P. mirabilis, P. vulgaris, and Y. enterocolitica. Further research is needed, especially in vivo experiments and evaluation of the cytotoxicity effect of CALEE. Keywords: Centella asiatica, Proteus mirabilis, Proteus vulgaris, Yersinia enterocolitica, antibacterial